Combustion synthesis and upconversion luminescence of CaSc_2O_4：Yb~（3＋）,Er~（3＋） nanopowders - 彭文芳 邹少瑜 刘关喜 肖全兰 孟建新 张蕤 (Journal of rare earths, 2011)
Novel up-conversion （UC） luminescent nano-powders, CaSc2O4：Yb3＋：Er3＋ were prepared with a combustion method at an ignition temperature as low as 200 oC. The CaSc2O4：Yb3＋,Er3＋ nano-powder had an orthorhombic CaFe2O4-type structure, and showed sphere-like morphology with an average diameter of about 30 nm. It gave strong green （525, 552 nm） and red （652–674 nm） up-conversion luminescence due to the 2H11/2→4I15/2, 4S3/2→4I15/2 and 4F9/2→4I15/2 transitions of Er3＋ under a 980 nm semiconductor laser excitation at room temperature. The optimized doping concentrations for Yb3＋ and Er3＋ were 6.0 mol.% and 1.0 mol.%, respectively. Effects of ignition temperature and glycine-to-metal nitrate molar ratio on up-conversion emission intensity were also investigated. The log-log plots of luminescence intensity and pump power revealed that the 652–674 nm red emissions and 552 nm green emissions belonged to a two-photon process, while the 525 nm green emissions belonged to a three-photon process. The possible UC mechanisms were briefly discussed.